Description of the collective behavior in competition of young soccer players under-16 (U-16), under-17 (U-17), under-19 (U-19), and under-23 (U-23), considering the areas of the pitch and phases of the game - Nieto, S.; Echeazarra, I.; Errekagorri, I.; Castellano, J. (The Journal of Strength and Conditioning Research, 2024)
The objective was to employ an integrated observational-notational record to describe collective behavior (CB) in competition matches of young soccer players from 4 teams, U-16, U-17, U-19, and U-23, playing for a professional soccer club academy. A total of 1,481 possessions were registered. Collective behavior, captured by GPS devices, was described with the variables: depth, surface area, stretch index, length, and width. In addition, from the notational analysis, the behavior depending on the area of the field (Z1, Z2, Z3, and Z4) and ball possession (POS), nonball possession (nPOS), and set pieces phases were contextualized. A 2-tailed analysis of variance was applied to compare the CB of the teams. Results show that: (a) in all ages/categories, CB varied significantly in and without the possession of the ball and was conditioned by the area of the pitch where the ball was; (b) CB showed higher values with the ball and greater variability without it; and (c) depending on the age, CB presented differences with larger effect sizes in depth and length, in and without the possession of the ball, in Z1 and Z2. Integrating positional data to the moment of play and areas of the field could help a more accurate analysis of the competition to better understand the CB evolution of young soccer players.